The Role of Communication Government in Advancing Culture for the Preservation of Jaipong Dance - Nurazhari, Luthfiah; Nuraeni, Reni (PERSPEKTIF, 2025)
Dance is a national identity that reflects a culture that must be preserved, but one of the Sundanese dances, namely jaipong, currently requires a strategy in maintaining its existence. This study aims to examine the role of government communication in efforts to preserve the art of Jaipong dance in the city of Bandung. The problem is focused on the effectiveness of government programs in maintaining sustainability and developing Jaipong dance in the midst of globalization. This research uses the theory of government communication in the promotion of culture. The data were collected through in-depth interviews and analyzed qualitatively. This study concludes that government communication through programs such as training, performance facilitation, coaching, and international promotion has made a significant contribution to the preservation of Jaipong dance. However, the study also identified several challenges, such as the lack of optimal quality of certification and the expansion of community participation. The results of this study provide important recommendations for the government, art actors, and the community in a joint effort to preserve the nation's cultural heritage.